Welcoming without reserve?: a case in Christian hospitality - Reynolds, Thomas E. (Theology today, 2006)
In an interconnected and diverse world, Christians are called to hospitality. Yet this is no easy matter, for welcoming the stranger requires becoming vulnerable. A particular case in Christian hospitality illustrates the point. Hosting a Jewish funeral, a church community elected to cover its sanctuary's cross. While such an action can be seen as scandalous, an act of bad faith, I argue instead that it embodies hospitality - scandalous, indeed, but in a positive sense. On several accounts, this instance of covering the cross opens up new ways of thinking about being Christian in a religiously diverse world.